Challenges for Business Actors Micro, Small, and Medium Enterprises (MSMEs): Duck Snack Village - Dhiya, Inas; Mei, Diyah; Candra, Puput; Amalia, Shinta; Wibisono, Marshall; Putri, Natasya; Oktaviano, Sefian; Furqon, Chusnul; Irma, Ade (Sahwahita: Community Engagement Journal, 2025)
Kampung Jajan Berbek Village, Sidoarjo Regency, is an MSME center area that focuses on the production and sale of traditional cakes involving around 30 business actors who produce from their respective homes. This study aims to identify the main challenges faced by MSME actors in carrying out their business activities, especially related to aspects of financial recording, access to capital, and utilization of digital technology. The method used in this study is a qualitative approach through field observation and semi-structured interviews with MSME actors. The study results show that most MSME actors still do not have an adequate financial recording system, some of which do not even record at all. In addition, limitations in accessing capital and low utilization of social media as a means of promotion are the main obstacles to business development. Based on these findings, this study recommends the need for intensive training in financial management and digital marketing, as well as facilitation of sustainable access to capital to support improving the performance and competitiveness of MSMEs in Kampung Jajan Berbek Village.